International perspectives on leading low-performing schools - Meyers, Coby V.; Darwin, Marlene (Emerald Publishing Limited : Information Age Publishing, Inc., 2018)
"Research is clear: School leadership quality matters. However, our knowledge of effective school leadership remains limited in at least three substantial ways. First, our understanding of school leadership effectiveness generally and school principal effectiveness specifically is limited to Western contexts, primarily North America and western European ones. Second, even in the confines of Western research and context, there has been relatively little specific focus on effectively leading low-performing schools. Third, even the conceptualization of leadership--do we mean the school principal, an administrative team, or a broader school leadership team--is a key factor in how we define and respond to the challenge of leading in low-performing schools. This book advances discussion and disseminates knowledge and global perspectives on what school leadership looks like, how it is enacted and under what circumstances, and when or where lessons might be portable. We anticipate this book having wide appeal for researchers, policymakers, and practitioners considering school leadership and how to support it effectively. The chapters suggest a noticeable level of convergence globally on how to lead low-performing schools effectively. Yet, there are clear political and culture differences that add significant gradation to how school leaders might enact best practice locally or inform policymakers and systems leaders about how to set up school leaders for success and subsequently support them. This book is one of the first that prioritizes the universality and nuance of leading low-performing schools globally"-- Provided by publisher.
Keywords: Educational leadership.; Low-performing schools.; School improvement programs.; Educational change.; Education -- General.; Schools and pre-schools.; Education.; elektronické knihy; electronic books